2007
DOI: 10.1124/jpet.107.126045
|View full text |Cite
|
Sign up to set email alerts
|

15d-Prostaglandin J2 Inhibits Inflammatory Hypernociception: Involvement of Peripheral Opioid Receptor

Abstract: The 15-deoxy-⌬ 12,14 -prostaglandin J 2 (15d-PGJ 2 ) is an endogenous ligand of peroxisome proliferator-activated receptors ␥ (PPAR-␥) and is now recognized as a potent anti-inflammatory mediator. However, information regarding the influence of 15d-PGJ 2 on inflammatory pain is still unknown. In this study, we evaluated the effect of 15d-PGJ 2 upon inflammatory hypernociception and the mechanisms involved in this effect. We observed that intraplantar administration of 15d-PGJ 2 (30 -300 ng/paw) inhibits the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 41 publications
6
46
0
9
Order By: Relevance
“…Other cyclopentenone prostanoids that contain one or two electrophilic carbons (12-PGJ 2 , 8-iso PGA 2 , PGA 2, PGA 1 ) mimicked the TRPA1-activating effect of 15dPGJ 2 , whereas their structurally related precursors lacking electrophilic carbons (PGD 2 , PGE 2 ) failed to do so, indicating the importance of electrophilic moieties for TRPA1 activation (474,715). It is worth mentioning, however, that 15dPGJ 2 has been reported to inhibit carrageenan-or PGE 2 -induced mechanical hyperalgesia and formalin-evoked overt nociception (528,566). It was proposed that 15dPGJ 2 activated opioid peptide-expressing macrophages via peroxisome proliferator-activated receptor gamma receptors and that the released opioids then produced local antinociception.…”
Section: Effects Of Inflammatory Mediators On Peripheral Nociceptorsmentioning
confidence: 78%
“…Other cyclopentenone prostanoids that contain one or two electrophilic carbons (12-PGJ 2 , 8-iso PGA 2 , PGA 2, PGA 1 ) mimicked the TRPA1-activating effect of 15dPGJ 2 , whereas their structurally related precursors lacking electrophilic carbons (PGD 2 , PGE 2 ) failed to do so, indicating the importance of electrophilic moieties for TRPA1 activation (474,715). It is worth mentioning, however, that 15dPGJ 2 has been reported to inhibit carrageenan-or PGE 2 -induced mechanical hyperalgesia and formalin-evoked overt nociception (528,566). It was proposed that 15dPGJ 2 activated opioid peptide-expressing macrophages via peroxisome proliferator-activated receptor gamma receptors and that the released opioids then produced local antinociception.…”
Section: Effects Of Inflammatory Mediators On Peripheral Nociceptorsmentioning
confidence: 78%
“…Pharmacological activation of PPAR-γ in the brain and spinal cord rapidly inhibits the spinal transmission of noxious inflammatory signals and local edema. These results suggest that PPAR-γ plays an important role in pain modulation in the central nervous system (Morgenweck et al, 2010) as well as in peripheral tissues and in peripheral endings of somatic afferents (Napimoga et al, 2008a;Pena-dos-Santos et al, 2009).…”
Section: Discussionmentioning
confidence: 95%
“…PPAR-γ agonists represent a promising therapeutic alternative for inflammatory diseases (Chima et al, 2008;Cuzzocrea et al, 2003;Kaplan et al, 2005;Napimoga et al, 2008aNapimoga et al, , 2008bPena-dos-Santos et al, 2009;Shan et al, 2004) and, in particular, they are extremely neuroprotective (Collino et al, 2006;Hyong et al, 2008;McTigue et al, 2007;Park et al, 2007;Pereira et al, 2006;Sundararajan et al, 2005;Tureyen et al, 2007;Zhao et al, 2005Zhao et al, , 2006. PPAR-γ was observed to be more expressive in ischemic neurons in rats with transient cerebral ischemia, suggesting that neuronal injury might alter PPAR-γ signaling (Victor et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, our and other research groups have demonstrated the anti-inflammatory activity of exogenously administered 15d-PGJ 2 (12)(13)(14)(15)(16)(17)(18). However, it has been estimated that .50% of the 15d-PGJ 2 added exogenously to a biological system binds to albumin (11).…”
Section: {‖mentioning
confidence: 99%